ANALISIS PENGGUNAAN BAHASA SARKASME PADA KOMENTAR NETIZEN DI MEDIA SOSIAL INSTAGRAM - dan Wahyu Asriyani, Lyswidia Andriarsih (Sasando, 2020)
This study is to describe the language of netizens when using social media, which mostly uses sarcasm. The benefit is that netizens are wiser in speaking in social media because what they are talking about is not necessarily the truth. This study uses a methodological approach. The methodological approach is divided into two, namely a qualitative approach and a descriptive approach. The qualitative approach is an approach that uses arguments in sentences. The descriptive approach in this study is used to provide an orderly description and one or more dependent variables in a particular group, so that it can find the speaker's intentions either explicitly or implicitly behind his speech. The results of this study are deviations in social media, one of which is due to the form of sarcasm language. Sarcasm language if used not at the right time and place can hurt someone's feelings.